Notas sobre Neófitas 4. Polygonum empálense (Polygonaceae), una planta invasora Nueva para México - Vibrans, Heike; Hanan Alipi, Ana María (Instituto de Ecología, A.C., 2008)
Polygonum nepalense Meisn. (= Persicaria nepalensis (Meisn.) H. Gross), Polygonaceae, of Asia is reported as new to Mexico. Two populations were found in high-altitude areas of the State of Mexico, and they appear to be in expansion. The species is known as an aggressive weed, with high impact on various crops, and also as an invader of natural vegetation. As the invasion seems to be recent and incipient, an eradication effort is recommended.